Negosiasi Performativitas Pedagogis Pembelajaran Musik Generasi Z - Bahaudin, Imam; Juwariyah, Anik; Yanuartuti, Setyo (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Abstract: This study identifies and explores the negotiations that occur as pedagogical performativity in learning music in the digital era for Generation Z. This study also looks at the performativity of conventional to modern music learning. Furthermore, it can be known and clarified the position of music learning and its flexibility in learning modern music for generation Z. This type of research is qualitative with a case study approach. Data were obtained with questionnaires in qualitative research, and interviews, which were taken from April 2020 to January 2021. The data sources were 100 music teachers in Surabaya and Sidoarjo, East Java. The research point of view uses the concept of children's musical aspects popularized by Schu-Fang Lin and Helena Gaunt (2016) about the pedagogy of 21st Century music learning. The results show that performativity and pedagogical negotiation in Generation Z music learning begins with awareness and learning innovations carried out by teachers. The teacher realizes that the entry of technology has a significant role in the learning process of music. Negotiation of performativity and pedagogy ultimately leads to a multidimensional learning model that has a reciprocal effect on students. Multidimensional learning highlights the advantages of embracing technology for music learning for Generation Z without obscuring the traditional and other essential aspects of music and conventional learning. The use of technology and the negotiations that occur in it raises multidimensional learning, which aims to include aspects of the face-to-face classroom learning experience with technology-based learning experiences to become an attraction for Generation Z in music learning.Keywords: negotiating, performativity, pedagogy, music learning, Generation ZÂ Â Â